2018
DOI: 10.1111/fima.12223
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sovereign Risk: Are CDS Spreads Better than Sovereign Credit Ratings?

Abstract: Using data for 54 countries over a 12‐year period, we find that the variation in average sovereign ratings in a given year can be explained by average credit default swap (CDS) spreads over the previous three years. In a horse race between CDS spreads and sovereign ratings, we find that CDS spread changes can predict sovereign events, while rating changes cannot. The predictability of CDS spreads is greater when there is disagreement between Moody's and the S&P for a country's rating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…We control for various country-level and global factors that can influence a country's sovereign risk (Edwards, 1983;Rodríguez, Dandapani, & Lawrence, 2019) in the estimations. Data on country-level controls, namely, GDP per capita, inflation, current account balance, GDP growth, and total reserves (excluding gold) as a percentage of imports, are obtained primarily from the World Bank's World Development Indicators (WDI) database.…”
Section: Datamentioning
confidence: 99%
“…We control for various country-level and global factors that can influence a country's sovereign risk (Edwards, 1983;Rodríguez, Dandapani, & Lawrence, 2019) in the estimations. Data on country-level controls, namely, GDP per capita, inflation, current account balance, GDP growth, and total reserves (excluding gold) as a percentage of imports, are obtained primarily from the World Bank's World Development Indicators (WDI) database.…”
Section: Datamentioning
confidence: 99%
“…A recent study prepared by Rodriguez et al (2019) asked if CDS spreads are better than sovereign credit ratings in measurement of credit risk. Based on findings CDS spread changes could predict sovereign crises that will come within next seven months, nonetheless ratings do not have such a predictive ability.…”
Section: Iliterature Reviewmentioning
confidence: 99%
“…This case stems from the smoothed ratings caused by policy adopted by rating agencies which delays rating changes. Rodriguez et al (2019) conclude that CDS spreads, which are available and less costly to collect compared to macroeconomic data, is useful to market participants.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The sovereign credit risk represents the probability that a government might be unable to meet its debt obligations in the future. According to Rodríguez et al (2019), credit default swap (CDS) spreads measure sovereign credit risk better than sovereign credit rating. Using data for 54 countries over twelve years, they found that CDS spread changes can predict sovereign events while rating changes cannot.…”
Section: Introductionmentioning
confidence: 99%